Effect of Dietary Intake of Lutein Rich Foods on the Retina and its Associated with Retinopathy Among Diabetic Patients - Hiba Raad Saeed; Ahmed Ghazi Dadoosh; Besmah Mohamad Ali; Khaled Awad Mohamed Elbassiouny (Diyala Journal of Medicine, 2024)
Background: Diabetic retinopathy (DR) is a common micro-vascular consequence of diabetes mellitus that affects the eyes. If untreated, DR cause damage to the retinal blood vessels and result in blindness or visual loss Hyperglycemia over long period of time results in increases inflammatory oxidative stress and protein kinase C pathways that eventually retinal capillary endothelial damage and pericyte loss occurred. Lutein is a carotenoid with anti-inflammatory and antioxidant properties. Objective: To determine the protection roles of dietary intake of lutein rich foods on the retina and it’s associated with retinopathy among diabetic patients. Patients and Methods: A cross-sectional study was conducted in the Ophthalmology Department of Imamein Kadhimein Medical City, Baghdad, Iraq, from July to November 2023, involving a total of 100 diabetic patients. Questionnaire list was used which consist of sociodemographic information, socioeconomic status, dietary sources of lutein, anthropometric measures and ophthalmic examination and investigations which include optical coherence tomography for macular assessment and HbA1c assessment. Results: The current study showed that 64% of the diabetic patients had retinopathy and 36% had normal retina. The study showed that 91.7% of diabetic patients with normal retina were consume 3-7 serving/week tomato, 75% were consume 7-35 serving/week egg, 75% were consume 1-7 serving/week zucchini, 72% were consume 1-3 serving/week spinach, 63.9% were consume 3-7 serving/week green pepper, 63.9% were consume 3-7 serving/week basil, 61% were consume 3-7 serving/week parsley, 58% were consume 3-7 serving/week leek, 52.8% were consume 3-7 serving/week lettuce, 41.7% were consume 1-2 serving/week nut and 30.6% were consume 1-2 serving/week pistachio with significant p-value. Conclusion: Patients with diabetes can avoid retinal damage by consuming the recommended weekly servings of lutein-rich foods especially tomato, eggs, zucchini, spinach, green pepper, basil, parsley, leek, lettuce, nut and pistachio. Keywords: Diabetic retinopathy, lutein, visual impairment.